2023
DOI: 10.1038/s41598-023-36643-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between circulating tumour DNA and skeletal muscle stores at diagnosis of pancreatic ductal adenocarcinoma: a cross-sectional study

Abstract: Low skeletal muscle index (SMI) and low skeletal muscle radiodensity (SMD) are associated with reduced survival time in pancreatic ductal adenocarcinoma (PDAC). The negative prognostic impact of low SMI and low SMD is often reported as independent of cancer stage when using traditional clinical staging tools. Therefore, this study sought to explore the relationship between a novel marker of tumour burden (circulating tumour DNA) and skeletal muscle abnormalities at diagnosis of PDAC. A retrospective cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…The study was approved by the Human Research Ethics Committee of Monash Health (Monash Health HREC Ref: 15450A and 17387L). As mentioned earlier, a subset of these patients has been previously published in a study examining the correlation between body composition and myopenia 50 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was approved by the Human Research Ethics Committee of Monash Health (Monash Health HREC Ref: 15450A and 17387L). As mentioned earlier, a subset of these patients has been previously published in a study examining the correlation between body composition and myopenia 50 …”
Section: Methodsmentioning
confidence: 99%
“…We recently assessed the relationship between ctDNA and the incidence of myopenia at diagnosis, in patients with pancreatic cancer. This study found that whilst ctDNA correlated with clinical stage, myopenia did not 50 . In this study, we aim to expand this patient cohort and release more comprehensive findings to better assess whether ctDNA can be an accurate diagnostic and strong prognostic marker through the investigation of its sensitivity, specificity, correlation with tumour size and prognostic capabilities across all stages of disease.…”
mentioning
confidence: 99%